Anticipating the times. From the theory of ideas to exercising movements - Andorlini, A. (EWF Scientific Magazine, 2016)
The work of some of scholars, researchers and practitioners has been somewhat predictive. By anticipating the times, these pioneers of movement have built a structure of thought and an operating patrimony, able to support the evidence of their insights. Thanks to them, and to their work, we have the possibility of drawing closer to the essence of movement, establishing a rational continuum which links cognition processes to motor operations.From the teachings of each of these "pioneers", we can acquire significant elements, correlated to the development of a theory, which is not born, ipso facto, but which, formed by the dissemination of an overall thought, has been gradually enriched with various contributions. A theory that has intervened to define the current direction in the field of training, restoring the correct relationship between real movement and the ideal exercise, between artificial exercise and natural movement.